"Człowiek mówiony". Społeczni "aktorzy" jako produkty praktyk dyskursywnych = "Spoken people". Social "players" as products of discourse practices - Zimniak, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Communication is not just an exchange of information, but also a construction of information. Discours has a significant impact on cultural meanings and social configurations.
Keywords: dyskurs; komunikacja; system; skrypt; znaczenia kulturowe i społeczne; discourse; communication; script; cultural and social meaning